Menstrual disorders and occupational exposures among female nurses: A nationwide cross-sectional study. (July 2019) - Jiang, Zhaoqiang; Wang, Jing; Guo, Xinnian; Feng, Lingfang; Yu, Min; Zhou, Jianhong; Ye, Yan; Mei, Liangying; Ju, Li; Yu, Dandan; Shi, Li; Lu (Alex), Chensheng; et al.
Abstract: Background: The regularity of menstrual cycles is one of the important indicators of female reproductive health. However, the current evidence on the association of occupational exposures and menstrual disorders is scarce. Objectives: This study aims to elucidate the relationship between occupational hazards and menstrual characteristics in female nurses and non-nurse health care workers in China. Design: We conducted a national cross-sectional study on the reproductive health of female nurses in China. Settings: A total of 1, 300 medical institutions in 15 provincial administrative regions in China participated in the study. Participants: There were 8, 904 nurses and 3, 977 non-nurse health care workers who were selected using simple random sampling method. Methods: All participants were administered a face-to-face standardized questionnaire, including personal socio-demographic information, occupational activities, and self-reported menstrual characteristics. Univariate and multivariate logistic regressions were used for statistical analyses. Results: The results demonstrated that 41% of nurses experienced menstrual disorders. We found handling disinfectants was the most significant risk factor for menstrual disorders ( OR = 1.53, 95% CI : 1.39–1.68), followed by abnormal workload ( OR = 1.28, 95% CI : 1.19–1.39), and occupation as a nurse ( OR = 1.28, 95% CI : 1.18–1.40). Noise, prolonged standing or frequent heavy lifting, night work, anti-cancer drug exposure, and overtime work were moderately associated with the occurrence of menstrual disorder ( OR > 1). Conclusions: This national-wide cross-sectional study has revealed the significant association between menstrual disorders and occupational hazards among female nurses in China.